Reproductive Biology of Channa micropeltes Cuvier, 1831 from the Lubuk Siam Lake, Siak Hulu District, Kampar Regency, Riau Province - Qorry Tillawati Fani; Deni Efizon; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTRed snakehead fish (Channa micropeltes) is one of freshwater fish species that inhabit the Lubuk Siam lake. A study aims to understand the reproductive biology of C. micropeltes has been conducted. The fish was sampled 3 times, once/month, from January to March 2018. Parameters measured were sex ratio, gonad maturity level, Gonad Somatic Index (GSI), fecundity and egg diameter. Results shown that there was 23 males and 31 females captured and the sex ratio was 1:1. Size at maturity in male was 241 mm (SL), while that of the females was 200 mm (SL). The males were in the 2nd and 3rd maturity levels, while that of the female were in the 2nd, 3rd, and 4th maturity levels. The GSI of male ranged from 0.05-1.13% while that of the females was 0.06-2.39%. The fecundity was 10.455-14.198 eggs/female and egg diameter was 1.3-1.7 mm. Keywords: Sex ratio, gonad maturity level, gonad somatic index, fecundity